Reading minds: A study of deictic shifts in translated written interaction between mental-health professionals and their readers - Pedro Ricoy, Raquel de (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The practice of knowledge mediation in written texts relating to the health sciences has hitherto received limited attention within Translation Studies. The overall aim of this study is to explore writer-reader interaction in a bilingual corpus of medical leaflets published on the website of the Royal College of Psychiatrists (UK). In order to do this, a comparative analysis of English source texts and Spanish target texts was conducted to identify shifts in personal reference, which served to contrast patterns in knowledge transfer processes between mental health experts and their target audiences. The study is underpinned by Thompson and Thetela’s (1995) tenet that interactive and interactional features have to be considered in conjunction. It seeks to make a contribution to the relatively understudied field of how interaction patterns differ across cultural and linguistic settings. The corpus is of special interest due to the sensitivity of its subject matter, the varied constituency it addresses and the fact that the translated texts were produced and revised by mental health professionals.